Intersectoral Synergy Strategy to Improve the Image of Educational Institutions (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to analyze the intersectoral synergy strategies implemented by Madrasah Aliyah Negeri (MAN) Bondowoso in enhancing its institutional image. The image of an educational institution is not only shaped by academic achievements but also by its ability to build participatory and sustainable collaboration across multiple sectors. This research employs a qualitative descriptive approach, using in-depth interviews, participatory observation, and documentation studies involving the principal, teachers, students, and external partners such as government agencies, private sectors, and local media. The findings reveal three main strategies in developing intersectoral synergy: (1) External communication strategy, which emphasizes open, accommodative, and participatory relationships with stakeholders; (2) Program collaboration strategy, implemented through joint activities such as digital literacy training, environmental awareness programs, and student entrepreneurship initiatives; and (3) Media publication strategy, which utilizes social media, the official school website, and local news outlets to strengthen the institution’s brand image. These strategies have proven effective in building public trust, social legitimacy, and internal pride among the members of the madrasah community. The study concludes that intersectoral synergy is not merely a tool for improving educational quality but also a strategic instrument for constructing a positive, modern, and inclusive institutional image of Islamic educational institutions.